Decision Support System for Identifying Priorities of Social Assistance for Poor Families Using the Simple Additive Weighting (SAW) Method in RW 05 Kramat Jati, East Jakarta - Rizky Rezaldi, Mohamad; Susano, Adhi; Frijuniarsi, Nurul (Yayasan Meira Visi Persada, 2024)
This research aims to design a decision support system for poor families, which can determine the priority of social assistance in Rw 05, Kramat Jati, East Jakarta. Using the simple additive weighting (SAW) method to produce accurate and fast decisions. Using the java programming language and MySQL database, and developing a decision support system in accordance with predetermined criteria. The data collection methods used are interviews and observations. From this research, it can be concluded that the application of the Decision Support System for Identifying Priorities for Social Assistance for the Poor in Residents of Rw 05 Kramat Jati, East Jakarta with the Simple Additive Weighting (SAW) Method is expected to increase the efficiency and effectiveness of determining recipients of social assistance carried out by the head of Rw 05 in Kramat Jati, East Jakarta. In addition, this system also increases the accuracy of data calculations so that the decision to determine social assistance recipients in Rw 05 Kramat Jati, East Jakarta can be determined more precisely